Agroinfiltration contributes to VP1 recombinant protein degradation. Issue 6 (1st November 2016) - Pillay, Priyen; Kunert, Karl J.; van Wyk, Stefan; Makgopa, Matome Eugene; Cullis, Christopher A.; Vorster, Barend J.
ABSTRACT: There is a growing interest in applying tobacco agroinfiltration for recombinant protein production in a plant based system. However, in such a system, the action of proteases might compromise recombinant protein production. Protease sensitivity of model recombinant foot-and-mouth disease (FMD) virus P1-polyprotein (P1) and VP1 (viral capsid protein 1) as well as E. coli glutathione reductase (GOR) were investigated. Recombinant VP1 was more severely degraded when treated with the serine protease trypsin than when treated with the cysteine protease papain. Cathepsin L- and B-like as well as legumain proteolytic activities were elevated in agroinfiltrated tobacco tissues and recombinant VP1 was degraded when incubated with such a protease-containing tobacco extract. In silico analysis revealed potential protease cleavage sites within the P1, VP1 and GOR sequences. The interaction modeling of the single VP1 protein with the proteases papain and trypsin showed greater proximity to proteolytic active sites compared to modeling with the entire P1-polyprotein fusion complex. Several plant transcripts with differential expression were detected 24 hr post-agroinfiltration when the RNA-seq technology was applied to identify changed protease transcripts using the recently available tobacco draft genome. Three candidate genes were identified coding for proteases which included the Responsive-to-Desiccation-21 (RD21) gene and genes for coding vacuolar processing enzymes 1a ( Nb VPE1a) and 1b ( Nb VPE1b). The data demonstrates that the tested recombinant proteins are sensitive to protease action and agroinfiltration induces the expression of potential proteases that can compromise recombinant protein production.